REGULARITIES OF COOLIGOMERIZATION OF C9 FRACTION AND HEAVY PYROLYSIS TAR MONOMERS - Gnativ, Zoriana; Nykulyshyn, Irena; Voronchak, Taras; Rypka, Anna (Proceedings of National Aviation University (archive), 2014)
Regularities of cooligomerization of С9 fraction of diesel fuel pyrolysis and heavy pyrolysis tar withcationic polymerization catalyst - AlCl3, have been investigated. The obtained cooligomer yield and physicochemicalproperties dependences on the C9 fraction/heavy pyrolysis tar ratio and process conditions have been studied. Theoptimal conditions have been determined.